Learning to be a lord, a friend, 'a human': Lord Snooty as a comic strip representation of John Macmurray's philosophies of social and emotional learning. Issue 1 (1st July 2020) - Pursall, Dona
Friendship was a central motif of 'Lord Snooty and His Pals', a comic strip created by Dudley Dexter Watkins for the launch of DC Thomson's new children's weekly, Beano, in July 1938. The Lord and his working-class friends were motivated by their relationship to overcome boundaries in order to play and learn together. This close analysis of strips from the first year of the comic explores the ways in which friendship is depicted, illuminating the extent to which social learning is pivotal to the child reader's pleasure. This examination is framed within educational thinking from the time. It specifically draws from Scottish philosopher John Macmurray's notion of 'valuational knowledge', which contends that interrelational social compassion, developed through friendships, promotes our capacity for wisdom and rationalization. As one of the many humanist progressives of education at the time, he argued that it is through our companionships that we learn what we need to know in order to live socially. Through appreciation of the ways in which learning and compassion are portrayed in these comics, this article wishes to align these strips with both educational concerns from the 1930s, such as Macmurray's, and further to draw attention to the relevance of this discussion in the light of renewed interest raised, for example, by Richard Gerver's Education: A Manifesto for Change (2019) and as enacted by policies such as Scotland's Curriculum for Excellence (2010). Through a study of comics for children, this article compares pedagogic ideas from the 1930s with contemporary discourse related to childhood, learning and compassion.